Estratégia de Purificação de Links Virtuais para Redes de Entrelaçamento Quânticas - Tavares, David; Abreu, Diego; Abelém, Antônio (Anais do Simpósio Brasileiro de Computação e Comunicação Quânticas (SBCCQ); 2026: Anais do I Simpósio Brasileiro de Computação e Comunicação QuânticasDO - 10.5753/sbccq.2026.23032, 2026)
End-to-end entanglement distribution in multi-hop quantum networks experiences fidelity degradation as entanglement swapping progresses over noisy and heterogeneous channels. In this paper, we propose a virtual-link purification strategy in which multiple EPR pairs are used at each stage to create virtual links between non-adjacent nodes and then purified in cascade using symmetric purification. The approach allows parameterizing the number of links per stage and follows a hierarchical design, with a more complete first stage and simplified purification in subsequent stages. We implement a time-slot-based orchestrator and compare the proposal against conventional swapping under Werner and bit-flip noise models. The results indicate higher end-to-end fidelity with virtual-link purification.